Pengaruh Posisi Pronasi terhadap Derajat Keparahan Acute Respiratory Distress Syndrome (ARDS) pada Pasien Covid-19 - Setiyawan Setiyawan; Wahyu Rima Agustin; Noviana Nur Zaidah (Universitas Faletehan, 2022)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease which can be exacerbated by Acute Respiratory Distress Syndrome (ARDS), multiple organ failure, septic shock, and acute heart failure requiring intensive care. Prone position can play its role in the prevention of those impairments. This study aimed to describe the role of prone position in the management of Covid-19 patients. This is a quantitative study with a quasi-experimental and one group pre-test post-test design. The samples were 32 covid-19 patients treated in Intensive Care unit (ICU) with Non-Invasive Ventilation (NIV) as respondents selected by a consecutive sampling technique. The data analysis used Wilcoxon test. The instruments were Lung Injury Score (LIS) and the parameter result observation sheets from the bedside monitors. The results showed that prone position could reduce the severity of ARDS in COVID-19 patients. Prone position can be recommended as a nursing intervention in adult COVID-19 patients who experience respiratory disorders.